Patients' experiences of the treatment BeWell™, in a primary care context. - Segerström, Maria; Gunnarsson, A. Birgitta; Hörberg, Ulrica; Wagman, Petra (Scandinavian Journal of Occupational Therapy, 2025)
Background: Stress-related illnesses are increasing in society, impacting people's abilities and well-being. The treatment for these in Sweden is provided in primary health care, but more treatment methods are needed. The newly developed individual health-promoting treatment 'Photo-supported conversations about well-being' (BeWell™) has shown improvements for this group. Occupational therapists have been positive about its use, but knowledge is also needed about how the patients perceive it. Aim: To describe the participating patients' experiences of the BeWell™ treatment. Materials and methods: A qualitative approach was applied in the study, in which 35 patients (aged 29–62 years) in primary health care who were diagnosed with stress-related illness participated. The interviews focus on the participants' experiences of BeWell™ and were conducted after completing the treatment. The data were analyzed using qualitative content analysis. Findings: Three categories were identified, expressing the participants' experiences of participating in BeWell™: 'The combination of the core parts gives strength', 'Influences on the experience', and 'Contribution to enhanced everyday life'. Each category encompassed two or three sub-categories. Conclusions and significance: BeWell™, provided by occupational therapists, was perceived to impact positively on the participants' health, well-being, and everyday life. Combinations of the different components of the treatment generated value beyond that of each part on its own.